BILANGAN KROMATIK LOKASI UNTUK GRAF AMALGAMASI BINTANG - Fadhilah Syamsi (Jurusan Matematika FMIPA Universitas Andalas Padang, 2013)
Let G = (V; E) be a connected graph and c a coloring of G. For i = 1; 2; :::; k,we dene the color classes Cias the set of vertices receiving color i. The color code c(v)of a vertex v 2 V (G) is the k-vector (d(v; C1); d(v; C2); :::; d(v; Ck)), where d(v; C) isthe distance between v and C. If all vertices of G have distinct color codes, then c iscalled a locating-coloring of G. The locating-coloring number of graph G, denoted byLi(G), is the smallest positive integer k such that G has a locating coloring with k color.Let K1;nibe star, where niis the number of leaves of each star K. We dene thevertex amalgamation of star, denoted by Sk;(n1;:::;nk)1;n, as a graph obtained from starsKby identifying one arbitrary leaf from each star. We dene the edge amalgamationof star, denoted by S1;nik;(n, as a graph obtained by uniting an edge of each star.If ni1;:::;nk)= m for each i, then we denoted the vertex amalgamation of star as Sandthe edge amalgamation of star as Sk;m. In this paper we discuss the locating coloring ofSk;(n1;:::;nk)and Sk;(n1;:::;nk).